Stand up for your life - "Richardson, Cheryl" (London, 2002)
Cheryl Richardson believes that today we face a crisis of spirit and a longing for a sense of purpose that will give meaning and direction to our lives. This crisis, caused by a disconnection from our inner selves, leaves us feeling empty and lost. In this book, she hopes to address the recurring problems that she's witnessed during her years of coaching clients and speaking to self-help audiences throughout the world. Part mentor, part friend, she picks up where "Take Time for Your Life" and "Life Makeovers" left off in this practical, step-by-step plan that should help to build confidence and eliminate self-defeating behaviours. By learning new self-honouring skills, like setting boundaries with grace and love or developing greater self discipline, readers should then be better able to own and use their unique talents and gifts.
Keywords: Self psychology